2009
DOI: 10.1080/10852350902735759
|View full text |Cite
|
Sign up to set email alerts
|

Using Organizational Collaboration and Community Partnerships to Transition Families from Homelessness to Home Ownership: The HomeBuy5 Program

Abstract: For more than a decade, the HomeBuy5 Program has successfully helped families who were homeless find an apartment, while working with them to develop a plan to move from homelessness to homeownership. This article provides an historical overview of how the program developed and evolved, a detailed discussion of the program's process and structure, the role of organizational collaboration and community partners, and demographic information on the families that have been served. It is argued that this program ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Solving A c c e p t e d M a n u s c r i p t 8 socially based problems is the underlying intention of social innovation. Likewise, collaboration has been found to be a key aspect in case study research on social change within organizations that result in improvements to service delivery models and outcomes for service users (Davey & Ivery, 2009;Gutierrez, Glenmaye, & DeLois, 1995;Mulroy, 1997Mulroy, , 2000Rogers, 2009). …”
Section: The Inter-organizational Context Of Direct Practicementioning
confidence: 95%
See 1 more Smart Citation
“…Solving A c c e p t e d M a n u s c r i p t 8 socially based problems is the underlying intention of social innovation. Likewise, collaboration has been found to be a key aspect in case study research on social change within organizations that result in improvements to service delivery models and outcomes for service users (Davey & Ivery, 2009;Gutierrez, Glenmaye, & DeLois, 1995;Mulroy, 1997Mulroy, , 2000Rogers, 2009). …”
Section: The Inter-organizational Context Of Direct Practicementioning
confidence: 95%
“…While previous research has pointed out the importance of collaboration in creating social change (Nichols, 2006), it tends to consider collaboration as a uniquely positive construct and one that is measured by the extent to which organizations are collaborating (Davey & Ivery, 2009;Gutierrez, Glenmaye, & DeLois, 1995). It is also important to consider the quality and the level of interconnectivity between organizations, as these aspects of collaboration can impact the willingness of organizations to engage in integrated social change efforts (Hodges & Hardiman, 2006;Sandfort, 1999).…”
Section: The Inter-organizational Context Of Direct Practicementioning
confidence: 98%
“…A few strategies leading to successful collaborations include open, frequent, on-going communication (Elder et al, 2013;Johnson, Zorn, Yung Tam, Lamontagne, & Johnson, 2003), partner-ready leadership (Austin et al, 1999;Johnson et al, 2003;Minkler, Vasquez, Tajik, & Peterson, 2008), and a clear research purpose or agenda (Davey & Ivery, 2009). During a collaborative partnership with the local community, the San Diego Prevention Research Center found that open communication lines lead to quality input and feedback from all partners (Elder et al, 2013).…”
Section: Strategies To Create Successful Collaborations and Partnershipsmentioning
confidence: 99%
“…The emergent interest is in how collaborations and partnerships between community service agencies, universities, and governmental agencies can address social and other problems in thoughtful ways. Collaboration is a decision-making process between two or more organizations (Davey & Ivery, 2009) usually uniting separate groups to achieve a mutual goal (Reilly, 2001). These relationships occur for various reasons including shared vision (Wolff, 2001), opportunity (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation